Pelatihan Penggunaan Website BKM Sedap Malam Kepada Anggota BKM Sedap Malam Penataban Kecamatan Giri - Taufiq, M.; Dedi, Mohammad; d, m (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2024)
The BKM Sedap Malam is an institution located in Penataban village that serves as a platform for activists to improve the local economy. Despite having numerous work programs, the institution faces challenges in disseminating data on its activities. To address this issue, the BKM Sedap Malam has created a website to distribute its work programs. However, the operators assigned to manage the website lack the necessary skills to do so effectively. To address this, the BKM Sedap Malam is providing training as part of community service to members on how to use the website effectively.